Embedded Systems for Smart Appliances and Energy Management - Grimm, Christoph; Neumann, Peter; Mahlknecht, Stefan (Embedded Systems, 2013)
This book provides a comprehensive introduction to embedded systems for smart appliances and energy management, bringing together for the first time a multidisciplinary blend of topics from embedded systems, information technology and power engineering.  Coverage includes challenges for future resource distribution grids, energy management in smart appliances, micro energy generation, demand response management, ultra-low power stand by, smart standby and communication networks in home and building automation.   Provides a comprehensive, multidisciplinary introduction to embedded systems for smart appliances and energy management; Equips researchers and engineers with information required to succeed in designing energy management for smart appliances; Includes coverage of resource distribution grids, energy management in smart appliances, micro energy generation, demand response management, ultra-low power stand by, smart standby and communication networks in home and building automation.  .